Oral tranexamic acid for an additional 24 hours postoperatively versus a single preoperative intravenous dose for reducing blood loss in total knee arthroplasty: results of a randomized controlled trial (TRAC-24). (1st October 2021) - Magill, Paul; Hill, Janet C.; Bryce, Leeann; Martin, Una; Dorman, Al; Hogg, Rosemary; Campbell, Christina; Gardner, Evie; McFarland, Margaret; Bell, Jennifer; Benson, Gary; Beverland, David
Abstract : Aims: In total knee arthroplasty (TKA), blood loss continues internally after surgery is complete. Typically, the total loss over 48 postoperative hours can be around 1, 300 ml, with most occurring within the first 24 hours. We hypothesize that the full potential of tranexamic acid (TXA) to decrease TKA blood loss has not yet been harnessed because it is rarely used beyond the intraoperative period, and is usually withheld from 'high-risk' patients with a history of thromboembolic, cardiovascular, or cerebrovascular disease, a patient group who would benefit greatly from a reduced blood loss. Methods: TRAC-24 was a prospective, phase IV, single-centre, open label, parallel group, randomized controlled trial on patients undergoing TKA, including those labelled as high-risk. The primary outcome was indirect calculated blood loss (IBL) at 48 hours. Group 1 received 1 g intravenous (IV) TXA at the time of surgery and an additional 24-hour postoperative oral regime of four 1 g doses, while Group 2 only received the intraoperative dose and Group 3 did not receive any TXA. Results: Between July 2016 and July 2018, 552 patients were randomized to either Group 1 (n = 241), Group 2 (n = 243), or Group 3 (n = 68), and 551 were included in the final analysis. The blood loss did differ significantly between the two intervention groups (733.5 ml (SD 384.0) for Group 1 and 859.2 ml (SD 363.6 ml) for Group 2; mean difference -125.8 ml (95% confidence interval -194.0 to -57.5; p < 0.001). No differences in mortality or thromboembolic events were observed in any group. Conclusion: These data support the hypothesis that in TKA, a TXA regime consisting of IV 1 g perioperatively and four oral 1 g doses over 24 hours postoperatively significantly reduces blood loss beyond that achieved with a single IV 1 g perioperative dose alone. TXA appears safe in patients with history of thromboembolic, cardiovascular, and cerebrovascular disease. Cite this article: Bone Joint J 2021;103-B(10):1595–1603.